Implementasi Sistem Android untuk Efisiensi Energi Listrik pada Ruangan Menggunakan Komunikasi Wireless - Syahid, Syahid; Santoso, Ari; Badruzzaman, Yusnan (Teknik Elektro - Politeknik Negeri Semarang, 2017)
Energy conservation efforts are applied at all stages of energy utilization, ranging from the initial utilization of energy resources to the final utilization, using efficient technology, and cultivate energy-saving lifestyle. The potential of energy conservation in all sectors have a huge savings opportunity, which is between 10% -35%. The savings can be realized in an easy way, can reach 10-15%, while saving the investment can reach up to 30%. With more efficient energy utilization can be achieved through: the use of energy-saving technologies; the application of energy-saving culture; application of energy conversion include planning, operation, and utilization energi.Pengontrolan supervision and monitoring energy usage can utilize evolving technologies today. Applications android based smartphone mainly grown very rapidly in various fields, one for control and of monitoring. This technology is used for the purpose of efficient use of energy, especially electrical energy. Features -Features and there yag system on smartphones support for controlling and monitoring energy usage. Smartphone can not work alone to be able to control and monitor but should be helped with some equipment that is connected directly to the peripheral controlled. Some of the equipment used is the PLC, sensor, power meter and wifi module.peralatan - dikendalikandan electrical equipment can be monitored in real time with wireless communication. The results obtained from the use of this technology can be used to monitor and control the use of energy in a space or building. Saving energy can also be done with the help of this system. Percentage savings can not be determined with certainty and further research is neededKey words: android, energy efficiency, wireless